Superiority of Admission Blood Urea Nitrogen over Serum Creatinine in Predicting In-Hospital Outcome of Patients with Acute Coronary Syndrome (Cardiovascular Journal, 2022)
Background: Serum creatinine and blood urea nitrogen (BUN) are the common markers of renal function and also one of the known predictors of adverse outcomes of acute coronary syndrome (ACS). The aim of this study is to assess the impact of elevated BUN on in-hospital outcome of ACS patients and superiority of BUN over creatinine for the assessment of in-hospital outcome in our setting.Methods: This prospective observational study with purposive sampling of a total of 184 patients was conducted from October, 2009 to September, 2010. Based on normal cut off values (BUN and serum creatinine was